Performance, carcass characteristics and non-carcass components of Texel × Santa Inês lambs fed fat sources and monensin - Soares, Sandro Braga; Furusho-Garcia, Iraides Ferreira; Pereira, Idalmo Garcia; Alves, Danilo de Oliveira; da Silva, Guilherme Rodrigues; de Almeida, Amélia Katiane [UNESP]; Lopes, Clenardo Macedo; Sena, Janaina Adna Barbosa (FapUNIFESP (SciELO), 2012)
Performance, carcass, non-carcass and commercial cuts and components of Texel × Santa Inês crossbred lambs, managed in confinement and fed diets based on soybean oil, soybeans and a conventional diet, with or without the use of monensin (78 ppm dry matter basis) were evaluated. Thirty-six Texel × Santa Inês lambs (18 males and 18 females) were managed in intensive systems. Animals were slaughtered after 87 days of confinement, and performance, carcass characteristics, weight and percentages of carcass and non-carcass components were evaluated. The animals fed the control diet had heavier carcass and parts than animals fed soybean, while the oil diet did not differ from the controls in most parameters. The animals fed soybean showed lower intake kg dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and metabolizable energy (ME) compared with animals fed the control diet, increased ether extract (EE) intake in kg, % body weight (BW) and metabolic weight (MW) and did not differ from the soybean oil diet. Animals receiving monensin had lower DM intake, OM, CP, EE, NDF, gross energy (GE) regardless of the expression, % kg BW, or % PM, than the animals that did not receive the additive. Males produced better and had heavier cuts than the females; the latter deposited subcutaneous fat earlier. Animals that received oil or soybean showed greater body weight and small intestine percentage. Soybean oil intake did not improve performance, carcass weights or parts of Santa Ines × Texel lambs in confinement. Soybeans at 15% dry matter reduced energy intake and lamb performance. The use of monensin at 78 ppm on a dry matter basis is not recommended for lambs in confinement, especially if associated with oil or soybeans that may harm animal performance. © 2012 Sociedade Brasileira de Zootecnia.
Keywords: Efficiency; Fat; Feed; Gain; Sheep; Weight